Faktor Penghambat Pelaksanaan Kurikulum Merdeka Pada Mata Pelajaran PPKn Di SMK Negeri 3 Kayuagung - Purnama, Mita; Rotari, Septi; Kartini, Kartini (Faculty of Teacher Training and Education of Undaris, 2025)
This study was conducted to identify the inhibiting factors in the implementation of the Merdekacurriculum in the Civics Education (PPKn) subject at SMK Negeri 3 Kayuagung. The data collection methodsused in this research were observation, interviews, and documentation. The data analysis techniquesemployed included data reduction, data presentation, and conclusion drawing/verification. Based on thedescription of the research findings, it was found that the inhibiting factors in the implementation of theMerdeka curriculum in the Civics Education subject were primarily internal factors. From the discussion ofthe research data, it can be concluded that internal factors play a significant role in the successfulimplementation of the Merdeka curriculum. Furthermore, the research findings suggest that the lack ofmotivation provided by teachers during the learning process, students' low curiosity and interest inknowledge related to the Merdeka curriculum, as well as teachers' limited knowledge and skills in teaching,are the main barriers to the effective implementation of the Merdeka curriculum at SMK Negeri 3Kayuagung.Keywords:, inhibiting factors, implementation, merdeka curriculum